Study on ageing process of cool coatings in tropical climate - Yang, Xingguo (2018)
Cool coating is an effective passive cooling technique for reducing the energy consumption of buildings and increasing thermal comfort of occupants. Its thermal performance is determined by two radiative properties, solar reflectance and thermal emittance. However, as cool coating ages, its solar reflectance and thermal emittance change, and consequently its thermal performance degrades. This thesis aims to investigate the ageing process and its effects on cool coatings. In this thesis, the thermal performance and energy saving benefits of cool coating were evaluated by field experiments in Singapore. Natural ageing experiments were conducted in Singapore, to record the changes of solar reflectance and thermal emittance of cool coatings in local environment. Then laboratory-based experiments were designed to quantify the effects of various environmental factors on cool coating, including soiling, cleaning, and ultraviolet (UV) radiation. Mathematical models for the changes of radiative properties of cool coatings during ageing were developed based on the results obtained in this thesis. Then they were embedded into an existing Cool Roof Heat Transfer (CRHT) model to improve the accuracy of heat transfer prediction. It shows that for the net heat gain of a test building for three years, the difference between the results from the two models could be up to 78%. Several kinds of cool coating were tested in this thesis, and it was found that the cool coating would experience less solar reflectance loss during ageing when they have improved surface properties, e.g., smoothness and omniphobicity. Future work such as investigation on soiling deposition rate in local climate could further improve the understanding of the effects of ageing on cool coatings.